Adolescent Distal Ulna Physeal Fracture with Extensor Retinaculum Interposition - Krishna, Sathya Vamsi; Bain, Greg (Journal of Wrist Surgery, 2023)
Background Isolated distal ulna fractures are rare injuries and are commonly associated with distal radius fractures. Though most of them can be managed conservatively, few of them require open reduction due to the interposition of various structures.Case Description In this case report, we report two cases of irreducible isolated distal ulna fractures in adolescents due to the interposition of the extensor retinaculum with its underlying tendons requiring open reduction to achieve bony union and distal radioulnar joint stability. These distal ulna fractures can be best reduced by open reduction with hypersupination and maintaining the distal ulna shaft gothic arch with pins.Literature Review There are very few case reports reported on isolated distal ulna fractures commonly seen in paediatric and adolescent patients leading to growth arrest. The interposition of various structures is a cause of irreducibility requiring open reduction. These fractures are equivalent to TFCC injuries in adults.Clinical Relevance  Whenever there is a gross displacement or difficult reduction interposition is to be considered. Open reduction of the fracture and maintenance of DRUJ congruity is sufficient without being critical on articular reduction.
Keywords: distal ulna fracture; irreducible isolated distal ulna fractures; extensor tendon; extensor retinaculum interposition; DRUJ stability; adolescent